Freezing and rejuvenation of human O erythrocytes for use in the immune adherence hemagglutination test. - Lawrence, T G (1985)
A method was established to freeze selected human O erythrocytes and to thaw them as necessary for use in the immune adherence hemagglutination test. This method ensured interrun reproducibility and eliminated the necessity to screen blood donors (fresh cells) for acceptable C3b receptor site sensitivity.